Social return on investment (SROI) for “New Permanent Housing” (RKB) project in Kuala Krai, Kelantan - Teo, Wei She (2022)
In December 2014, Malaysia was hit by a massive flood that brought long-term social, economic, and environmental impacts to both individuals and communities. These impacts therefore lead to a decision being made by the Malaysian government to establish a flood recovery project named “New Permanent Housing” (RKB). Indeed, almost everyone agrees that RKB project enhances people‟s lives and generates social benefits. However, there is insufficient evidence to support this, and there is no consensus on what that return is or how it might be measured. In this regard, social return on investment (SROI) can give a clear and succinct message about the project‟s impacts by assessing social, economic and environmental values. This study uses analyses of specific case studies as a guiding thread to demonstrate how the application of SROI can help identify the project‟s social added value and the changes experienced by key stakeholders. The four (4) objectives of this study are to identify the key stakeholders in the RKB project; define relevant data for demonstrating the impact map for the RKB project; evaluate the SROI on the implemented RKB project in Kuala Krai, Kelantan; and propose the use of the SROI method by the Malaysian government to assess the social benefits of investing in flood management projects. Research instruments such as key informants interview (KII), survey questionnaire (SQ), library search, and evidence from existing literature or projects were used. A total of 162 household units from four RKB projects in Kuala Krai, Kelantan, and three representatives from the Malaysian Federal Government (NADMA and JKR) were selected as the respondents. The qualitative and quantitative data were analysed by using SROI analysis. The results of this research show that investing in RKB projects generates an SROI of more than 1.0 in social value for the beneficiaries and provides a range of opportunities to support the sustainable development of communities. Therefore, it was concluded that SROI is applicable to government flood recovery projects in Malaysia, which will help to reveal the hidden sustainable value of changes in social investment.